2004
DOI: 10.1213/01.ane.0000111101.41190.99
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Assessment of Cerebral Autoregulation in Subarachnoid Hemorrhage

Abstract: The moving correlation coefficients between slow changes of arterial blood pressure and mean or systolic flow velocity, termed "Mx" and "Sx," respectively, characterize cerebral autoregulation but have not been applied to subarachnoid hemorrhage. A study in 15 patients revealed that Mx and Sx were significantly increased, indicating impaired autoregulation during vasospasm as compared with baseline, as well as on the side of vasospasm in comparison with the contralateral side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 41 publications
3
106
0
Order By: Relevance
“…The mean flow index, Mx, which is derived from mean FV and CPP and its noninvasive version, Mxa, where ABP is used instead of CPP, have been previously investigated in patients with SAH. 3,35 In the present study, we have used an alternative index derived from systolic values of FV as previously described. 13,31,32 In one study of 32 patients with SAH changes in autoregulation during vasospasm were identified more accurately with Mx than with Sx.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean flow index, Mx, which is derived from mean FV and CPP and its noninvasive version, Mxa, where ABP is used instead of CPP, have been previously investigated in patients with SAH. 3,35 In the present study, we have used an alternative index derived from systolic values of FV as previously described. 13,31,32 In one study of 32 patients with SAH changes in autoregulation during vasospasm were identified more accurately with Mx than with Sx.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…13,31,32 In one study of 32 patients with SAH changes in autoregulation during vasospasm were identified more accurately with Mx than with Sx. 35 However, a cohort study of 300 patients with head injury showed that Sxa had a stronger association with outcome than Mxa. 31 Relationship of Continuous Indices, Sxa and TOxa, with Transient Hyperemic Response Ratio Both Sxa and TOxa showed good accuracy for predicting impaired autoregulation as seen by a THRR of p1.09, without significant differences between the two methods.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Disturbed autoregulation has been shown to be associated with unfavorable outcome after head injury [9], vasospasm after subarachnoid hemorrhage [10], and the possibility to use autoregulation to define an individual target for cerebral perfusion pressure is suggested (recommendation, level III) in the latest edition of the Brain Trauma Foundation Guidelines for the management of severe traumatic brain injury [11].…”
Section: Abpmentioning
confidence: 99%
“…Thus, inappropriate volume loading or periods of spontaneous or induced hypertension may aggravate brain edema. However, awareness of autoregulation as an important protective mechanism for patients with SAH and traumatic brain injury increases [10,11,25,46,47].…”
Section: Head Elevation and Cerebral Hemodynamicsmentioning
confidence: 99%
“…The indices of autoregulation are calculated as moving correlation coefficients between spontaneous slow changes in MAP and slow changes in systolic (systolic index; Sx) or mean (mean index; Mx) flow velocities (FV), which can be used as indicators of autoregulation [11,37,46]. The higher the FV, the more impaired the cerebral autoregulation [46]. The pressure reactivity index (PRx), described by Czosnyka et al [10], measures the correlation between ABP and ICP waves and may reflect cerebral autoregulation in response to blood pressure changes.…”
Section: Head Elevation and Cerebral Hemodynamicsmentioning
confidence: 99%